Comparative toxicotranscriptomics of longterm cypermethrin exposure to aquacultured fish Labeo catla (Catla) - Basanta Kumar Das; Satabdi Ganguly; Anupam Adhikari; Subhasree Subhasmita Raut; Smruti Priyambada Pradhan; Subir Kumar Nag; Kavita Kumari; Vikash Kumar (Scientific Reports)
Abstract Cypermethrin (CYP), a persistent synthetic pyrethroid, poses a significant threat to aquatic life. The present work aims to identify the effect of CYP on the brain and liver transcriptome profile of fish Labeo catla. CYP (0.7 µg/L) was long-term exposed to L catla, and differentially expressed genes (DEGs) were investigated using RNA-sequencing (Illumina HiSeq2500). A total of 2665 and 18,020 unigenes and 333 and 454 DEGs were identified in the brain and liver transcriptome, respectively. DEGs associated with MAPK signaling and apoptosis pathways were co-expressed in both brain and liver transcriptome, according to pathway enrichment analysis. Concurrently, steroid and terpenoid backbone biosynthesis were overexpressed in liver, suggesting induction of apoptosis and steroid production, respectively. Among the identified DEGs, fosab, nr4a1, dhcr24 and tm7sf2 were significantly enriched and molecular docking studies further supported our findings. Long-term CYP exposure also altered the levels of antioxidant enzymes superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), and malondialdehyde (MDA) content in L. catla. The present study provides significant insights into the consequences of CYP-induced toxicity in fish and identified functional genes that could be screened for estimating the toxic load of CYP in future ecotoxicological risk assessment studies.